Pharmacist-led Si-care (schizophrenia care) model to improve medication adherence and symptom management in schizophrenia - Noor Cahaya; Susi Ari Kristina; Anna Wahyuni Widayanti; James A. Green (Elsevier, 2024)
Introduction: Schizophrenia is a chronic mental disorder that requires long-term treatment, particularly antipsychotic medications. However, medication adherence among patients with schizophrenia is often suboptimal, leading to symptom relapse and poor outcomes. The Si-Care (Schizophrenia Care) program was developed as a pharmacist-led home intervention to improve medication adherence and support symptom control in patients with schizophrenia. This study aimed to evaluate the effectiveness of the Si-Care intervention in improving medication adherence and maintaining stability of symptoms among schizophrenia patients. Methods: A quasi-experimental study was conducted in three community health centers or Puskesmas in Banjarmasin, Indonesia. A total of 57 participants were recruited according to the sampling criteria. The Si-Care intervention consisted of seven home visits by trained pharmacists over four months, providing education, counseling, and medication monitoring. Adherence to medication was evaluated using the pill count method and severity of symptoms was measured using the Positive and Negative Syndrome Scale (PANSS) pre- and post-intervention. Data were analyzed using the Friedman test for adherence and the Wilcoxon test for PANSS scores. Results: Mean medication adherence improved significantly from 77.38 % ± 25.85 at baseline (T0) to 97.57 % ± 11.09 at the final visit (T4) (p = 0.000). However, the decrease in PANSS scores from 38.03 ± 9.14 to 37.81 ± 9.15 was not statistically significant (p = 0.089). Despite the lack of significant change in PANSS scores, symptoms remained stable throughout the intervention, suggesting effective symptom management. Conclusions: The Si-Care intervention significantly improved medication adherence among people with schizophrenia, contributing to the maintenance of stable symptoms. Pharmacist-led home interventions provide valuable support to address adherence challenges and should be considered a critical component in schizophrenia care. Future studies should consider a more rigorous design, a larger sample size, and longer follow-up to better evaluate the sustainability, scalability, and applicability of the intervention in diverse healthcare settings.